Stagpression: The economic and financial impact of the COVID-19 pandemic - Mario Arturo Ruiz Estrada; Evangelos Koutronas; Minsoo Lee (Contemporary Economics, 2021)
This paper formulates an analytical framework to understand the spatiotemporal patterns of epidemic disease occurrence, its relevance, and implications to financial markets activity. The paper suggests a paradigm shift: a new multi-dimensional geometric approach to capture all symmetrical and asymmetrical strategic graphical movement. Furthermore, it introduces the concept of stagpression, a new economic phenomenon to explain the uncharted territory the world economies and financial markets are getting into. The Massive Pandemic Contagious Diseases Damage on Stock Markets Simulator (φ-Simulator) to evaluate the determinants of capital markets behavior in the presence of an infectious disease outbreak. The model investigates the impact of Covid-19 on the performance of ten stock markets, including S&P 500, TWSE, Shanghai Stock Exchange, Nikkei 225, DAX, Hang Seng, U.K.-FTSE, KRX, SGX, and Malaysia-FTSE.
Keywords: R11; R12; 330; Stagpression; Pandemics; economic modeling; economic desgrowth; policy modeling; Stock Market